Analisis Komparasi Metode Sistem Pendukung Keputusan pada Gaya Belajar “VARK” - Riani, Ambar; Taswanda Taryo; Achmad Hindasyah (UNIVERSITAS INDO GLOBAL MANDIRI, 2023)
Learning style is an important factor in the success of the learning process from learning resources to individuals or groups. Understanding learning styles can be a strategy in the learning process. One of the learning styles is